Quality physicochemical and textural of strawberry, pepper and maltodextrin jams (Research, Society and Development, 2020)
The objective of this study was to promote the development of strawberry jellies with young finger pepper, also determining the influence of the addition of maltodextrin on its physicochemical and textural properties. Four formulations were made using different maltodextrin concentrations (0, 5, 10 and 15%). The jellies were evaluated with respect to physicochemical parameters (moisture content, water activity, total solids, total soluble solids, ashes, proteins, lipids, ascorbic acid, total titratable acidity, ratio and pH) and instrumental texture profile (firmness, cohesiveness, adhesiveness, chewing and chewing). The results were statistically analyzed using a completely randomized design, whose means were compared by Tukey test. Through the obtained results, it was verified the viability in the use of strawberry and pepper for the production of jelly, all the samples are adequate to the quality standard established by the legislation. The addition of maltodextrin increased pH, soluble solids, ratio and vitamin c, showed opposite behavior regarding moisture content, water activity and acidity. Regarding the texture, it was found that the increase of maltodextrin caused the decrease of the parameters of firmness, adhesiveness, gummy and chewable and increased cohesiveness of the samples.